Local traditional knowledge and global climate change - Cruz Hernández, Sergio; Torres Carral, Guillermo Arturo; Cruz León, Artemio; Salcedo Baca, Irma; Victorino Ramírez, Liberio (Revista Mexicana de Ciencias Agrícolas, 2020)
Local traditional knowledge or knowledge is closely related to the culture of the communities, social relationships and their ecosystems, they represent the worldview of Mesoamerican peoples. This is how the knowledge of the climate throughout history has always been present in different ways: agricultural calendar, cabañuelas, the type and shape of clouds, it can be seen that climate change has been affecting the biological cycles of the plants and animals and the human being and modifying this knowledge. The main objective is an analysis of the way of life inherent to the traditional knowledge in the agriculture of basic grains in the Sierra Alta region of Hidalgo. The methodology that was implemented is with a qualitative approach, the method is deductive, with a descriptive study, for the collection and analysis technique a structured survey was applied. It is concluded that this knowledge is seriously threatened, due to acculturation processes, given that the population adopts new cultural patterns, outsiders to them, abandoning or forgetting ancestral knowledge, this limits adaptation, mitigation and combat to Climate Change at the local level and global.